1989
DOI: 10.1126/science.2569236
|View full text |Cite
|
Sign up to set email alerts
|

Brain Region and Gene Specificity of Neuropeptide Gene Expression in Cultured Astrocytes

Abstract: Astrocytes have many neuronal characteristics, such as neurotransmitter receptors, ion channels, and neurotransmitter uptake systems. Cultured astrocytes were shown to express certain neuropeptide genes, with specificity for both the gene expressed and the brain region from which the cells were prepared. Somatostatin messenger RNA and peptides were detected only in cerebellar astrocytes, whereas proenkephalin messenger RNA and enkephalin peptides were present in astrocytes of cortex, cerebellum, and striatum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
92
0
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(101 citation statements)
references
References 26 publications
8
92
0
1
Order By: Relevance
“…The present results confirm and extend previous reports by localizing proenkephalin mRNA in astrocytes at the cellular level by in situ hybridization, and thereby provide direct evidence that the enkephalin mRNA previously identified in Northern blots is expressed by astrocytes and not by a small number of contaminating non-astrocytic cells which are present in the astrocyte-enriched cultures reported in previous studies 37, 43,52 . In particular, cells double-labeled for both proenkephalin mRNA and GFAP intermediate filaments provide first direct evidence that astrocytes express the proenkephalin gene during development.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present results confirm and extend previous reports by localizing proenkephalin mRNA in astrocytes at the cellular level by in situ hybridization, and thereby provide direct evidence that the enkephalin mRNA previously identified in Northern blots is expressed by astrocytes and not by a small number of contaminating non-astrocytic cells which are present in the astrocyte-enriched cultures reported in previous studies 37, 43,52 . In particular, cells double-labeled for both proenkephalin mRNA and GFAP intermediate filaments provide first direct evidence that astrocytes express the proenkephalin gene during development.…”
Section: Introductionsupporting
confidence: 92%
“…These and other experiments suggest that endogenous opioids are normally available to cells in the developing CNS in sufficient quantities to tonically inhibit growth 17,18,41,[54][55][56] . In support of this hypothesis, opioid peptide levels and opioid binding are greatly increased in the rat cerebellum 48,49 28,32,43,52 . In the present study, proenkephalin (proenkephalin A) mRNA and enkephalin peptide expression were examined by in situ hybridization and immunocytochemistry, respectively, in primary cultures of the developing CNS (i) to identify the specific cellular sites of proenkephalin gene and peptide expression, and (ii) to determine whether opioids are expressed by replicating astrocytes prior to their reaching confluence.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Vilijn et al (1989) have recently demonstrated that cultured astrocytes can synthesize and secrete CPE. Cultured astrocytes from various brain regions can express peptide genes, including proenkephalin (Vilijn et al, 1988), somatostatin (Shinoda et al, 1989) and angiotensinogen (Stometta et al, 1988). Therefore, CPE may process neuropeptides in both neurons and glia.…”
Section: Discussionmentioning
confidence: 99%